Students' E-Learning Experience through a Synchronous Zoom Web Conference System - Dwi Rahayu (University of Muhammadiyah Prof. DR. HAMKA, 2020)
Synchronous e-learning is a distance learning through a real-time live web-conference platform. In this learning, students' reflection on their experience in using the system is beneficial to the overall success. This study explores students' experience and what they perceive from the implementation of synchronous e-learning through zoom conference system. Using exploratory sequential design, the data were collected from 62 students taking an English subject in a university in Indonesia. Classroom observations and a set of a questionnaire by a five-point Likert scale were used to collect the data. Findings from observations denote there are three factors of activities: communication, lesson material and study process. Findings from the questionnaire indicate positive answers from all three factors. The students agreed that they could communicate at ease before the lesson starts, question and answer during the study process, and could work collaboratively through the breakout rooms. Through the whiteboard/shared screen feature in zoom conference, students described that they were able to give feedback to each other. Moreover, they mostly agreed that materials to the lesson could be accessed and understood in e-learning. However, with all the positive feedback on the three factors, they agreed that the traditional face-to-face still gives easier and better access from the factors of communication and materials compared to the e-learning.